2012
DOI: 10.1073/pnas.1113455109
|View full text |Cite
|
Sign up to set email alerts
|

Salience network integrity predicts default mode network function after traumatic brain injury

Abstract: Efficient behavior involves the coordinated activity of large-scale brain networks, but the way in which these networks interact is uncertain. One theory is that the salience network (SN)-which includes the anterior cingulate cortex, presupplementary motor area, and anterior insulae-regulates dynamic changes in other networks. If this is the case, then damage to the structural connectivity of the SN should disrupt the regulation of associated networks. To investigate this hypothesis, we studied a group of 57 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
423
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(471 citation statements)
references
References 59 publications
42
423
1
5
Order By: Relevance
“…We have previously shown that after TBI, FA measurements in particular WM tracts relate to multiple neuropsychological domains 10, 11, 46. In a separate cross‐sectional cohort of patients after moderate–severe TBI and controls who were scanned once, we confirmed both lower SPCC FA and lower immediate verbal memory recall in patients after TBI compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously shown that after TBI, FA measurements in particular WM tracts relate to multiple neuropsychological domains 10, 11, 46. In a separate cross‐sectional cohort of patients after moderate–severe TBI and controls who were scanned once, we confirmed both lower SPCC FA and lower immediate verbal memory recall in patients after TBI compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…Variability in performance on Stroop inhibition switching was also recently observed among a large number of TBI cases who were studied with resting state functional connectivity MRI (rs-fMRI), task-oriented functional MRI (fMRI) and diffusion tensor imaging (DTI). 53 In that study, 20/46, (43%) performed poorly on the stop signal reaction time (SSRT) task, with slower response inhibition (higher SSRT). These cases with slower reaction times in the NoGo condition were observed to have failure deactivating the DMN, particularly the precuneus/posterior cingulate cortex (precu/PCC) portion.…”
Section: Executive Functionmentioning
confidence: 99%
“…The LED placement loci included, in part, a proposed paradigm to target nodes within the default mode network (DMN) and the salience network (SN), areas where functional connectivity MRI studies have reported abnormalities in TBI. 53 The LED placement loci also included dorsolateral prefrontal cortex (DLPFC), part of the central executive network (CEN). 54 Supplementary Figure 1 (see online supplementary material at http://www.liebertonline.com) shows the location of extracranial bone and suture landmarks on the skull, in relationship to approximate surface brain cortex areas.…”
Section: Screening Cognitive Testingmentioning
confidence: 99%
“…Color image is available online at www.liebertpub.com/neu implicated extensively in a network important for selecting salient stimuli and guiding behavior in coordination with multiple other brain systems, [68][69][70] and the structural integrity of this network has been found to be crucial for DMN functioning in severe TBI. 71 Given that concurrent modulations of the DMN and task-positive regions have been found to support task performance in healthy individuals, [72][73][74][75] an increase in antiphase synchrony during the clinical recovery period may signify a restoration of balanced network function necessary for efficient cognitive processing. In keeping with the view of the DMN and TPN as reciprocal networks, co-occurring internetwork (PCC-TPN) antiphase synchrony and residual intranetwork (PCC-DMN) synchrony may be two parts of a larger effect involving the modulation and optimal balancing of distributed networks.…”
Section: Venkatesan Et Almentioning
confidence: 99%